2015
DOI: 10.7555/jbr.29.20150052
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 and triglyceride-rich lipoprotein metabolism

Abstract: Pro-protein convertase subtilisin-kexin 9 (PCSK9) is known to affect low-density lipoprotein (LDL) metabolism, but there are indications from several lines of research that it may also influence the metabolism of other lipoproteins, especially triglyceride-rich lipoproteins (TRL). This review summarizes the current data on this possible role of PCSK9. A link between PCSK9 and TRL has been suggested through the demonstration of (1) a correlation between plasma PCSK9 and triglyceride (TG) levels in health and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Its function in these tissues may vary, indicating cell and tissue-specific roles. PCSK9 also affects triglyceride-rich lipoproteins, such as very VLDL and chylomicrons 19 . It can influence the production and secretion of VLDL and modulate the metabolism of intestinal chylomicrons, though its impact on plasma triglyceride levels is relatively modest compared to its effect on LDL-C. PCSK9 has garnered significant interest in its role in regulating lipoprotein(a) (Lp(a)), a lipoprotein-associated with an increased risk of CVD 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Its function in these tissues may vary, indicating cell and tissue-specific roles. PCSK9 also affects triglyceride-rich lipoproteins, such as very VLDL and chylomicrons 19 . It can influence the production and secretion of VLDL and modulate the metabolism of intestinal chylomicrons, though its impact on plasma triglyceride levels is relatively modest compared to its effect on LDL-C. PCSK9 has garnered significant interest in its role in regulating lipoprotein(a) (Lp(a)), a lipoprotein-associated with an increased risk of CVD 20 .…”
Section: Methodsmentioning
confidence: 99%
“…This tissue is the main storage site of triglycerides (TG). Several lines of evidence suggest that PCSK9 influences the metabolism TGrich lipoproteins (Druce et al 2015). Genetic ablation of the Pcsk9 gene in mice resulted in increased visceral adiposity due to elevated expression of the receptor for TG-rich very lowdensity lipoprotein (VLDLR) on the cell surface of adipocytes (Roubtsova et al 2011;Baragetti et al 2017).…”
Section: Local Versus Systemic Effect On Extrahepatic Tissuesmentioning
confidence: 99%
“…Patients with T1HLP generally present low LDL-C levels and HDL-C levels besides high TG levels (Fojo and Brewer, Frontiers in Genetics frontiersin.org 1992; Blom et al, 2018;O'Dea et al, 2019). Moreover, many studies have reported a potential correlation between plasma PCSK9 levels and LDL-C, but also triglycerides-rich lipoproteins and investigations linking these actors are being conducted (Lakoski et al, 2009;Druce et al, 2015;Norata et al, 2016;Baragetti et al, 2018;Warden et al, 2020). For these reasons, we measured plasma PCSK9 levels in the recruited members of the family.…”
Section: Pcsk9 Measurementsmentioning
confidence: 99%
“…Many studies have reported a potential correlation between plasma PCSK9 levels and LDL-C, but also TG, VLDL-C, and intermediate-density lipoprotein cholesterol (IDL-C). Investigations linking these actors of the lipid pathway are being conducted (Lakoski et al, 2009;Druce et al, 2015;Norata et al, 2016;Baragetti et al, 2018;Warden et al, 2020).…”
Section: Introductionmentioning
confidence: 99%